In Vitro Studies of Antiphospholipid Antibodies and Its Cofactor, β2-Glycoprotein I, Show Negligible Effects on Endothelial Cell Mediated Protein C Activation - Oosting, Janine D; Derksen, Ronald H W M; Hackeng, Tilman M; van Vliet, Marja; Preissner, Klaus T; Bouma, Bonno N; de Groot, Philip G (Thrombosis and Haemostasis, 1991)
The effect of sera and purified IgG isolated from plasma of 46 patients with systemic lupus erythematosus (SLE) and 9 healthy donors on the endothelial cell (EC) mediated protein C activation was investigated. Out of the 46 SLE sera used, 19 were antiphospholipid antibodies (aPL) positive. From 12 patients IgG was isolated, of which 6 contained aPL. EC were first incubated with IgG (7 mg/ml) or serum (1: 1 diluted) for 1 h and then tested for their ability to promote protein C activation by thrombin, with the cells either in a monolayer or in a suspension. The normal range (mean of control values ± 2 SD) of protein C activation was 80-120%. In contrast to others, we could not detect an inhibition of protein C activation by any of the patient IgG's or sera.The recently described cofactor for binding of antiphospholipid antibodies to phospholipids, β2-glycoprotein I, was purified and added to the purified IgG's. A combination of these two components did not inhibit the EC mediated protein C activation by thrombin.This study suggests that the inhibition of the protein C activation, mediated by EC, is not a general mechanism by which aPL related thrombosis can be explained.